(untitled) (The Pakistan Development Review, 2000)
The book begins with a comparison of the availability of public and private goods: “Cigarettes and soft drinks are available in just about every village but clean water, primary education or health services are not”. (Page 13). This thoughtprovoking statement by the author focuses the reader’s attention directly on the main subject of the book: the issue of private versus public management. The public sector is responsible for providing public services, i.e., delivery of those goods and services which the private entrepreneur is reluctant to provide. Consequently, the supply of those services is grossly inequitable and irregular, particularly in developing countries. One can find understaffed and ill-managed schools, polluted water, poor and unsafe means of transport and communication in such countries. People who are really in need of such services are deprived of them. For instance, often state primary schools are located in places where most of the population send their children to private schools. Public health units are available in areas where most of the people use private clinics. Electric power may be cut off for an hour in the richer parts of a city, but in the rural areas it is available for much shorter periods of time.